Coronary recanalisation, myocardial viability, and ventricular remodelling after infarction. Issue 4 (16th March 2005) - Camici, P G
Abstract : It is important to identify the mechanisms that determine the progression to left ventricular remodelling after an acute myocardial infarction, in order that patients can be treated before the development of overt heart failure